The (re) presentation of the Afro-diasporic subject in the music of the Calypsionan Walter Gavit Ferguson - López Céspedes, Sharon (2019)
In this article, the author analizes the situation of the Afro-Costa Rican identityin the Calypso, as a musical expression of the culture in the Province ofLimon in the Caribbean part of Costa Rica.